Examining the Relationship Between Digital Well-Being, Digital Hoarding and Mobile Information Security Awareness with Association Rule - Karabatak, Songul; Alanoglu, Muslim; Karabatak, Murat (Institute of Electrical and Electronics Engineers Inc., 2024)
The aim of this study was to investigate the relationships between digital well-being, digital hoarding, and mobile information security awareness. The study employed data mining methods and was conducted as a correlational study. Data collection involved the use of the Digital W ell-Being Scale, Digital Hoarding Scale, and mobile Information Security Awareness Scale. The study utilized data from a total of 466 students enrolled at the Faculty of Education of Firat University. The collected data underwent preprocessing techniques for data cleaning, transformation, and reduction. Descriptive and correlational analyses were carried out as essential components of the data analysis process. Descriptive analysis included calculating means, percentages, and frequency analyses. For correlational analysis, the association rule was employed to uncover relationships between variables. The results of the study indicated that university students overall exhibited a significant level of digital well-being. However, their awareness of mobile information security and inclination to hoard digital content were considered to be moderate. The findings revealed that individuals who were concerned about file deletion demonstrated considerate behavior towards other users on social media and recognized the impact of digital security on social media interactions. © 2024 IEEE.
12th International Symposium on Digital Forensics and Security, ISDFS 2024 -- 29 April 2024 through 30 April 2024 -- San Antonio -- 199532
Keywords: digital hoarding; digital well-being; mobile information security awareness